Reference interval for oxidative stress markers in young football and hockey players - Sarkar, S.; Dey, S. K.; Datta, G.; Bandyopadhyay, A. (Trends in Sport Sciences, 2023)
Introduction. Malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), and glutathione peroxidase (GPx) are widely accepted as biological markers for checking the redox balance and antioxidant status. Aim of Study. The purpose of the study was to frame the reference interval for antioxidant variables (MDA, SOD, GSH and GPx) in the young athletic population of various sports discipline. Material and Methods. 190 young male players [i.e., football (n = 89), and hockey (n = 101)] were recruited for the study (mean age = 18.3 ± 2.01 yrs). Assay of MDA, SOD, GAH and GPx was done by using the standard enzymatic protocol. Reference interval was calculated by following the Clinical and Laboratory Standard Institute (CLSI) C28-A3 guideline and MedCalc software (version 19) with a 90% confidence interval. Results. Serum MDA range was from 23.75-36.19 µmoles/100ml serum with mean of 30.29 ± ± 3.24 µmoles/100 ml serum and median around 30.43. Serum SOD ranged from 0.05-0.14 U/min/mg protein with mean of 0.08 ± 0.01 U/min/mg protein and median around 0.08. The GSH was ranging from 43.21-55.55 mg/100 ml serum with mean of 46.43 ± 2.11 mg/100 ml serum and median around 46.10. The GPx was ranging from 9.04-14.33 µmol/min/mg protein with mean of 11.35 ± 1.38 µmol/min/mg protein and median around 11.05. Conclusions. Present study confers 24.55- -35.58 µmoles/100 ml serum, 0.06-0.13 U/min/mg protein, 43.27- -51.86 mg/100 ml serum, and 9.07-14.12 µmol/min/mg protein as the reference interval values for MDA, SOD, GSH, and GPx respectively. The present finding will guide the researchers to avoid misinterpretation of antioxidant biomarker values during any phase of competitive training of sports person.